Successful Bilateral Penetrating Corneal Transplantation for Bilateral Vascularized Leucomas in the Outcome of Recurrent Keratouveitis (case report) - G. Sh. Arzhimatova; G. M. Chernakova; L. G. Estrin; E. V. Shirshova; A. S. Obrubov; M. Yu. Shemyakin; A. S. Slonimskaya; A. S. Chernakov (Oftalʹmologiâ, 2025)
Penetrating corneal transplantation or Penetrating keratoplasty (PKP) with native donor material is the method of choosing surgical treatment of purulent corneal ulcers with the threat of perforation or perforation, vascularized leucomas in the outcome of keratitis and keratouveitis, in these situations it is considered a high-risk keratoplasty for the development of graft disease. The pathological role of chronic inflammatory diseases of the nasopharynx and oral cavity as the cause of the formation of inflammatory pathology of the cornea, leading to corneal blindness, is little discussed at present. The publication describes a clinical case of successful phased bilateral UPC in a patient with bilateral vascularized corneal whiteheads in the outcome of recurrent keratouveitis, performed after complete rehabilitation of foci of infection in the oropharynx.